Determinants of preventive oral health behavior among senior dental students of Greater Noida, India - Ishan Prabhakar; K Jayaprakash; K K Shivalingesh; Bhuvandeep Gupta; Neha Gupta; Richa Anand (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral self-care practice is an effective preventive measure for maintaining good oral health. The health beliefs and attitudes of health professionals will not only affect their oral self-care habits, but will have a profound influence on their ability to motivate patients to learn and practice preventive oral health measures. Aim: The aim was to determine the preventive oral health behavior of senior dental students in relation to demography, knowledge of preventive care, and attitudes towards preventive dentistry. Materials and Methods: A cross-sectional study was conducted in a dental institution by distributing pretested questionnaire to 102 final year dental students. The overall response rate was 94%. Data were computed and tabulated. Statistical analysis was performed using Chi-square test using SPSS. Results: More than half of the respondents (56.25%) agreed that the frequency of sugar consumption has a greater role in producing caries. It was observed that 93.75% of students found preventive dentistry practice to be useful. Significant gender differences were observed in the use of recommended oral self-care, knowledge of using sealant as a caries preventive measure and fluoridation of drinking water as an effective way of preventing caries. Conclusion: There was an appreciably high level of good knowledge of preventive dental care among the dental students with a positive attitude towards preventive dentistry practice.